Perancangan UI/UX Aplikasi Mobile Pembelajaran Teks Naratif Berbasis Budaya Daerah Menggunakan Design Thinking - Khusnatul Amaliah; Muhammad Rakha Ramadhan; Dani Rofianto; Hastuti Retno Kuspiyah (Jurnal Minfo Polgan, 2026)
The function of mobile technology in education provides significant potential for students to learn independently; however, it is often restricted by rigid interface designs and a lack of local cultural content. The purpose of this study is to design a UI/UX prototype for an English narrative text learning application that integrates South Sumatran folktales, addressing the need for interactive and contextual teaching media. This study employs a Research and Development (R&D) method using the Design Thinking approach, which consists of five interactive phases: Empathize, Define, Ideate, Prototype, and Test. Through this process, key features such as Cultural Path, Interactive Story, and Word Box were developed. The testing results showed a task success rate of 98.5% and a user satisfaction score of 4.78 out of 5. a relatively high mis click rate (40.8%) was identified on the Learning Page feature, indicating the need for improvements in the navigation layout. The findings show that the application works effectively and is well received by users, although improvements in the navigation layout are still needed. This study demonstrates that Design Thinking helps improve usability and contextual learning in a culturally based narrative learning application.